Excitation of elastic oscillations in solids by a pulsed proton beam - Belan, V.; Butenko, V.; Ivanov, B.; Kolyada, Yu.; Fainberg, Ya.; Fedun, V.; Onishchenko, I.; Prishchepov, V.; Yegorov, A. (Вопросы атомной науки и техники, 1999)
At present, the beams of charged particles are used not only in fundamental researches but they have found a wide application in solving the plasma electronics problems, modification of material surfaces properties and in a number of other applications.